Modelos alternativos de financiamento ao desenvolvimento de produtos no setor farmacêutico - Luiza Pinheiro Alves da Silva (2021)
The focus problem of this thesis is the incompatibility between the determinants for innovation in the pharmaceutical innovation sector system and access to medicines, a fundamental element of the human right to health. On the economic side, the stimulus to innovation takes place through the guarantee of appropriation, mainly through monopolies; by public financing as innovative activities, in order to stimulate private investment; and by demand and estimated financial return, which is linked to consumer income. On the social side, the recognition of universal human rights determines that health is inseparable from the right to life, however, it is dependent on a market characterized by several flaws, which make access to health technologies extremely unequal between countries and within them. Pharmaceutical innovation is at the interface between these dimensions, as medicines are at the same time a product with high added value, coming from one of the most profitable industries in the world and an indispensable technology for healthcare. Financing is one of the determinants for innovation in the sector and one of the main bottlenecks. This problem has been discussed for nearly two decades in international multilateral forums, especially the WHO. An analysis was made of the current pharmaceutical innovation system, the WHO discussions on the subject and the initiatives implemented by this body for Covid-19. The emergence of new actors in the sector was observed, such as partnerships for product development and non-profit financiers. However, even with the disruption caused by the pandemic, the working dynamics of the pharmaceutical sectoral innovation system remained unchanged, privileging economic rather than health criteria, and high-income countries, from which originate the large global multinational companies. As a result, unequal access to medicines and other health technologies was maintained. Although there are proposals and guidelines reconciled in the international health forums for dealing with this problem, the implementation of mechanisms is not sufficient. It is necessary to reorient the pharmaceutical innovation system and its determinants in this sense, so that a new paradigm can be established.